2003
DOI: 10.1021/ac030182q
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Desalting Mass Spectrometry for the Study of Noncovalent Biological Complexes

Abstract: Electrospray ionization-mass spectrometry is becoming widely used as a high-throughput method for the study of biomolecular interactions. It allows for the analysis of complexes from heterogeneous mixtures with high sensitivity and selectivity. In many cases, biomolecules and their complexes must be stored in nonvolatile salt buffers and other solubilizing agents, such as organics or detergents, to maintain stability and integrity. To ensure an efficient electrospray process, desalting and exchanging the biomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 40 publications
0
77
0
Order By: Relevance
“…Unwanted adduct formation can be reduced by using microdialysis 15 or an in-line size-exclusion chromatography gel filtration cartridge. 16 Second, hydrophobic interactions are weaker in the gas phase than the liquid phase. 17 Third, the macromolecule must be soluble in a volatile buffer such as NH 4 OAc or NH 4 HCO 3 , which may be a problem for hydrophobic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted adduct formation can be reduced by using microdialysis 15 or an in-line size-exclusion chromatography gel filtration cartridge. 16 Second, hydrophobic interactions are weaker in the gas phase than the liquid phase. 17 Third, the macromolecule must be soluble in a volatile buffer such as NH 4 OAc or NH 4 HCO 3 , which may be a problem for hydrophobic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…PEEK column packed with BioRad P6 gel and using 20 mM ammonium acetate as the elution buffer via the automated system. This experimental set-up closely mimics the elution conditions described in the manual procedure described by Cavanagh et al [23]. The mass spectrum consists of three multiply protonated ions at m/z 1952, 2196, and 2510, which are consistent for heme-bound myoglobin.…”
Section: Resultsmentioning
confidence: 99%
“…A second approach was demonstrated by Cavanagh et al in which they used an in-line gel-filtration column directly coupled to a mass spectrometer [23]. This paper clearly demonstrated that the technique worked for protein-protein complexes and DNA-protein complexes that were stored in complex buffer solutions and showed an attractive solution to our problems for monitoring ligand exchanges.…”
Section: Ass Spectrometry (Ms) Is a Powerful Techniquementioning
confidence: 91%
“…Metal binding to B. subtilis Spo0F studied by lESI-MS lESI-MS (Loo 1997;Cavanagh et al 2003) was used to verify the Spo0F-metal ion binding trends observed in the 1 H-15 N HSQC NMR experiments. Shown in Figure 5 are the lESI-MS results of concentration-based experiments of four divalent metals studied: Mg 2+ , Ca 2+ , Mn 2+ and Cu 2+ at metal concentrations of 0, 125, 250 and 375 lM.…”
Section: Resultsmentioning
confidence: 99%